Modeling and Optimization of Increasing Teacher Innovativeness Based on Local Wisdom and Technological Literacy - Ponijan; Dian Wulandari; Soewarto Hardhienata (Jurnal Penelitian Pendidikan IPA, 2025)
Improving teacher innovation is a strategic effort to enhance the quality of education in Indonesia. This study aims to examine the factors influencing teacher innovation through a combination of exploratory and quantitative approaches. Five key variables were identified: organizational climate, spirit of cooperation, work motivation, transformational leadership, and digital technology literacy. A total of 180 foundation permanent teachers (GTY) from 20 private high schools in Bekasi Regency participated by completing questionnaires. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) and the Scientific Identification Theory for Operational Research in Education Management (SITOREM) method. The PLS-SEM results indicate a strong model fit with an R² of 0.767, predictive relevance (Q²) values above 0, Normed Fit Index (NFI) of 0.866, SRMR of 0.061, and better predictive accuracy than linear regression models. SITOREM analysis prioritized strategic improvements in teacher innovation, focusing on enhancing task responsibility, resource support, digital literacy, instructional media development, and scientific output. The findings contribute to targeted strategies for fostering teacher innovation and optimizing educational outcomes.